2019
DOI: 10.1002/eji.201847805
|View full text |Cite
|
Sign up to set email alerts
|

Impaired antigen‐specific lymphocyte priming in mice after Toll‐like receptor 4 activation via induction of monocytic myeloid‐derived suppressor cells

Abstract: In sepsis, the pathology involves a shift from a proinflammatory state toward an immunosuppressive phase. We previously showed that an agonistic anti‐TLR4 antibody induced long‐term endotoxin tolerance and suppressed antigen‐specific secondary IgG production when primed prior to immunization with antigen. These findings led us to speculate that TLR4‐induced innate tolerance due to primary infection causes an immunosuppressive pathology in sepsis. Therefore, the mechanism underlying impaired antigen‐specific hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…5,12,13,51 Such poorly immunogenic tumours could be targets of tumour vaccine therapy using an anti-TLR4 mAb. 32 Therefore, the efficacy of combinations of an anti-TLR4 mAb and checkpoint inhibitors, particularly an anti-PD-1 or -PD-L1 mAb, is of interest. Recently, we showed that administration of an anti-TLR4 mAb to mice in the Figure 7.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5,12,13,51 Such poorly immunogenic tumours could be targets of tumour vaccine therapy using an anti-TLR4 mAb. 32 Therefore, the efficacy of combinations of an anti-TLR4 mAb and checkpoint inhibitors, particularly an anti-PD-1 or -PD-L1 mAb, is of interest. Recently, we showed that administration of an anti-TLR4 mAb to mice in the Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse anti-mouse TLR4/MD-2 agonistic mAb (UT12) 38,39 was purified from conditioned serum-free medium (Hybridoma-SFM; Thermo Fisher Scientific, Waltham, MA) used to culture hybridomas. 32 Rat antimouse CD4 (GK1Á5), CD8 (YTS 169Á4Á2Á1) and PD-1 (RMP1-14) mAbs were purified from ascitic fluid of mice with severe combined immunodeficiency by caprylic acid precipitation followed by diethylaminomethyl ion-exchange chromatography. 26 Pam3CSK4 and low-molecular-weight poly(I:C) were from InvivoGen (San Diego, CA).…”
Section: Reagents and Absmentioning
confidence: 99%
See 3 more Smart Citations